"I Don't Like You Any More": Facebook Unfriending by Israelis During the Israel–Gaza Conflict of 2014. (1st December 2015) - John, Nicholas A.; Dvir‐Gvirsman, Shira
Abstract : This article explores Facebook unfriending during the Israel–Gaza conflict of 2014. We suggest that politically motivated unfriending is a new kind of political gesture. We present an analysis of a survey of 1, 013 Jewish Israeli Facebook users. A total of 16% of users unfriended or unfollowed a Facebook friend during the fighting. Unfriending was more prevalent among more ideologically extreme and more politically active Facebook users. Weak ties were most likely to be broken, and respondents mostly unfriended people because they took offense at what they had posted or disagreed with it. Although social network sites may expose people to diverse opinions, precisely by virtue of the many weak ties users have on them, our findings show these ties to be susceptible to dissolution.